TRANSFORMASI SOSIAL DAN EKOLOGIS PEREMPUAN PASCA PELATIHAN ECOPRENEURSHIP: STUDI KASUS SUSTAINABILITY SCOOL - Tan, Yunita (Jurnal Administrasi Bisnis, 2023)
This study explores the social and ecological transformation of women after participating in the ecopreneurship training program at Sustainability School (SScool), an educational community focused on environmental sustainability and women's economic empowerment. Using a qualitative phenomenological approach, this research examines alumni experiences in changing consumption patterns, increasing environmental awareness, developing sustainable businesses, and contributing to social empowerment within their communities. The findings reveal that SScool's training fosters more sustainable consumption habits, such as selecting natural materials for production, waste management, and reducing synthetic product usage. Environmental awareness has increased, reflected in the adoption of waste reduction principles and the growth of a circular economy mindset. Alumni have successfully developed sustainability-driven businesses, although challenges remain, such as high production costs and low consumer awareness of eco-friendly products. Socially, alumni act as change agents by sharing knowledge through training, business collaborations, and environmental education. Integrating critical pedagogy and constructivist theory, this study highlights the importance of experiential learning and social interaction in driving social change and supporting the achievement of Sustainable Development Goals (SDGs) in Indonesia. The study recommends strengthening support for women ecopreneurs through more inclusive policies and strategic partnerships to expand the impact of sustainable business ecosystems.